The phototactic rhythm of pests for the Solar Insecticidal Lamp: A review - Yao, Heyang; Shu, Lei; Yang, Fan; Jin, Yinghao; Yang, Yuli (Frontiers in Plant Science, 2023)
Pest management has been a great challenge since the beginning of human agricultural activities. Since the 1930s, chemical pesticide control has been a major control technology that can solve some of the pest problems in agricultural production. Still, it is harmful to food safety and the ecological environment. Meanwhile, the extensive use of chemical pesticides will lead to the rapid development of pest resistance and an increase in carbon emissions. Because of the advantages of low cost, friendly environment, and low side effects, Solar Insecticidal Lamp (SIL) as the main physical control technology has been widely used for pest management in agricultural production in China. Owing to the phototaxis of pests, most pests have a circadian phototactic rhythm during the nighttime, and fully exploring the phototactic rhythm of pests can help farmers and plant protection personnel to reasonably set the working time period of the insecticidal lamp at night. The purpose of this paper is to provide a comprehensive review of the pest phototactic rhythm in a selection of 24 pest species. So that, more people can know the phototactic rhythm of pests better. Moreover, this is the first comprehensive survey on the phototactic rhythm of pests accurate to the hour. In this paper, the phototactic rhythm of pests are studied in two different types of crops: 1) food crops and 2) economic crops. We also discuss and analyze the various factors (e.g., meteorological conditions, insecticidal devices, physiological states and others) that affect the changing phototactic rhythm of pests. Finally, we highlight some open research challenge issues and future directions.